PERANCANGAN WEBSITE SEKOLAH DASAR ISLAM TERPADU PERMATA BUNDA (SDIT-PB) GEDUNG MENENG RAJABASA BANDAR LAMPUNG - Mira Febriana Sesunan; Hartini (Jurnal Teknomatika, 2010)
In activity learn and study on SDIT-PB has connection books for evaluate activity students a days in school and in the houses. This book completed with teachers communication paper and the parents else paper is information study program for a week. For rapidly and clearly communication between students, parents and teachers needed to make systems has can to used by all element are connect. From that reason so has made a website with name design website for elementary school Islam Terpadu Permata Bunda (SDIT-PB) at Gedung Meneng Rajabasa in Bandar Lampung with content about information in SDIT-PB and data processing administration SDIT-PB with used PHP programming.